Optimalisasi Sumber Daya Manusia dalam Industri: Analisis Peran dan Strategi Pengembangan Keahlian dalam Meningkatkan Kinerja Sektor Perikanan - Muh. Ali Fikri Subair; Muhammad Nawir; Lisa Aulia Putri; Novia Damayanti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Indonesia has enormous marine and fisheries potential because of its vast sea area. Human resources in managing fishery products have not maximized the potential of fishery products. Therefore, in order to maximize the potential of fishery products, quality human resources are needed. Since human resources are an important part of an organization, including in the Indonesian fisheries industry, human resource management and development is very important for the success of an organization. The method used is qualitative research method, more precisely literature research. The literature research process is carried out by reviewing the literature and analyzing the relevant topics combined. Literature search can utilize sources in the form of journals, books, dictionaries, documents, magazines and other sources without conducting field research. The results found that in optimizing in improving the performance and sustainability of the fisheries product management industry, it is important to optimize human resources. Many approaches can be used to improve operational efficiency. Increase efficiency in all stages of production, from fishing to distribution, with the adoption of advanced technology and automated equipment. Training and Skills Development ensures that employees have a good understanding of the latest practices and technologies through regular training that enhances their technical and managerial skills. Good Production Planning and Management; Energy and Resources Management; Use of wise energy and resource management practices to reduce operational costs Partners and Collaboration: Work closely with suppliers, distributors, and relevant institutions to improve supply chain efficiency and coordination. Training and Skills Development ensures that employees have a good understanding of the latest practices and technologies through regular training that enhances their technical and managerial skills. Good Production Planning and Management; Energy and Resources Management; Use of wise energy and resource management practices to reduce operational costs Partners and Collaboration: Work closely with suppliers, distributors, and relevant institutions to improve supply chain efficiency and coordination.